Pengembangan Strategi Dakwah Dan Edukasi Ilmu Al-Qur'an Serta Bahasa Arab Bagi Masyarakat Urban: Pengabdian Kepada Masyarakat di Masjid Jami' Al-Fudhola Meruya Selatan Jakarta Barat - Ahyarudin; Fauziah, Ismi Latifah; Nurrahmah, AD Laila Khasanah; Hayyatunnasuha; Fahdah, Hasna Sahilah; Nursakilah; Reza, Rathaya Zayyan Shafyra; Al-Kholis, Salma Afifah Zayzafun; Fitriyah, Syifa (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2024)
The Qur'an is a sacred book in Islam and is the only Kalamullah that was revealed to the Prophet of the last days, namely the Prophet Muhammad SAW. The purpose of this community service is to explain and provide a snapshot of the Al-Qur'an's da'wah strategy and its various branches of knowledge, as well as applied by group 08 of the 2024 STIQ ZAD KKN women when carrying out Real Work Lecture activities in Meruya Selatan Village, Kembangan, West Jakarta. This service uses community service in the field. The results of this community service are increasing interest in reading and improving the reading of the Qur'an, increasing the awareness of the surrounding community about learning Arabic and Islamic science.